Creating Brochures as a Promotional Tool for Swiss-Belhotel Cendrawasih Biak - Sky Nicholas Wijanto; Ivonne Muliawati Harsono (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
The problem that Swiss-Belhotel Cendrawasih Biak has is the hotel brochure. The hotel brochure is unhighlighted in its USP, inconsistent in font, varied in colors, and poorly designed. This problem was caused by the hotel not prioritizing a well-designed and informative brochure. The solution was to create a brochure and improve the content of the brochure. The data collection method used was a questionnaire. The questionnaire involved 18 guests of Swiss-Belhotel Cendrawasih Biak. The main changes the writer made in the brochure are highlighting the USP, changing the font Sanz to Cinzel, making the font more consistent, using more concise words in the language, and using more consistent language in the brochure. By doing so, the writer helps the hotel increase the quality of its brochures and make them more consistent with their other promotional tools. As a result, the director of Swiss-Belhotel Cendrawasih Biak was very happy with the brochure.